Effect of yearly milk production on average days open - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1992)
Although there is a genetic antagonism between yearly production per cow and reproduction, analysis of Kansas Holstein herds suggests that managers of higher producing herds overcome this inverse relationship. Higher producing herds have fewer cows open at any given time, and those cows that are open average fewer days since last freshening. When open cows are categorized by days open, higher producing herds have fewer cows open more than 60 days, and especially fewer cows open more than 120 days.; Dairy Day, 1992, Kansas State University, Manhattan, KS, 1992;
Keywords: Dairy Day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-131-S; Milk production; Days open; Dairy cattle